The impact of greenwashing perception on green purchasing intentions: the mediating role of green trust, consumer brand engagement and green word-of-mouth and the moderating role of product involvement - Pacheco, Mariana Gomes (2022)
The growing attention to environmental problems all over the world made the market for green products to dramatically increase in recent years, turning green marketing in an important approach for firms to gain competitive advantage. However, as more companies are becoming aware of this competitive advantage, greenwashing behaviours started emerging, and consumers are becoming more sceptical towards companies green initiatives. Thus, this study explores whether and how consumers’ greenwashing perceptions influence their green purchasing intentions, by integrating the mediating role of green trust, consumer brand engagement, green word-of-mouth and the moderating role of product involvement. The research object of this study focuses on the answers of 302 consumers and utilizes partial least squares structural equation modelling to undertake an empirical study. The results indicate that consumers’ greenwashing perceptions do not have a direct negative impact on green purchasing intentions, but that this relationship is mediated by green trust and green word-of-mouth. Furthermore, a multi-group analysis also shows that product involvement moderates this relationship, as well as the mediators. Low involvement products appeared to experience stronger effects in comparison to high involvement products. Hence, this study suggests that companies should promote green initiatives that are clear, transparent and coherent, rather than greenwashing, in order to ensure better and long-lasting relationships with consumers and increase sales.